2004
DOI: 10.4049/jimmunol.172.11.7103
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Determinants of Outcome in Patients Undergoing Thoracoabdominal Aortic Aneurysm Repair

Abstract: Thoracoabdominal aortic aneurysm repair, with its requisite intraoperative mesenteric ischemia-reperfusion, often results in the development of systemic inflammatory response syndrome, multiorgan dysfunction syndrome (MODS), and death. In the present study, an adverse clinical outcome following thoracoabdominal aortic aneurysm repair was identified by blood leukocyte genomic and plasma proteomic responses. Time-dependent changes in the expression of 146 genes from blood leukocytes were observed (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 27 publications
(20 reference statements)
1
31
0
Order By: Relevance
“…Regarding outcome prediction and monitoring, several studies conducted in patients after surgery (171) or severe trauma (172)(173)(174) have shown promising results. We addressed this question in septic shock patients monitored after the early pro-inflammatory reaction, when the patient's immune functions are known to be severely depressed (>48 h after the onset of shock) (11).…”
Section: Toward a Genomic Approachmentioning
confidence: 99%
“…Regarding outcome prediction and monitoring, several studies conducted in patients after surgery (171) or severe trauma (172)(173)(174) have shown promising results. We addressed this question in septic shock patients monitored after the early pro-inflammatory reaction, when the patient's immune functions are known to be severely depressed (>48 h after the onset of shock) (11).…”
Section: Toward a Genomic Approachmentioning
confidence: 99%
“…54 Genomic and proteomic studies revealed that the levels of expression of 138 genes in peripheral blood leukocytes of patients undergoing thoracoabdominal aortic aneurysm repair and the concentrations of 7 plasma proteins discriminated between patients who developed multiorgan dysfunction syndrome and those who did not. 87 …”
Section: Cd3mentioning
confidence: 99%
“…Peripheral gene expression signatures have been shown to change acutely with surgery [4], and it is possible that some combination of "baseline" and "poststress" leukocyte profiles may be proven capable of predicting patients at high risk for complications with a known inflammatory component, such as atrial fibrillation or myocardial injury. Furthermore, leukocyte activation patterns may help gain mechanistic understanding of how inflammation is involved in the process of end-organ dysfunction (e.g., humorally mediated or cytotoxicity).…”
Section: How Do We Study Patients In the Perioperative Period?mentioning
confidence: 99%